Effect of Cu Doped Nickel Ferrites on Structural, Magnetic and Dielectric Properties. (2015) - Anjum, Safia; Rashid, Afshan; Bashir, F.; Pervaiz, Maryam; Zia, Rehana
Abstract: NiCu ferrites with the general formula Ni1-x Cux Fe2 O4, where x=0, 0.2, 0.4, 0.6, 0.8 have been synthesized by double sintering method. The single- phase spinel structure is confirmed by X-ray Diffractometer. This analysis showed the increasing behavior of lattice parameter due to the larger ionic radii of the Cu ion. Fourier transform infrared spectra confirmed the two prominent bands of spinel ferrites in the range (1000-400) cm -1 . Magnetic properties are studied using Vibrating Sample Magnetometer. It is investigated that the saturation magnetization decreases linearly as the copper concentration increases. The surface morphology is carried out using Scanning Electron Microscopy. The dielectric properties have been investigated as a function of frequency. The dielectric constant is decreased and AC conductivity is increased at higher frequency.